MULTILINGUALISM ACROSS BORDERS: NIGERIAREPUBLIC OF BENIN AS CASE STUDY - Babatunde, Samuel Olufemi (European Scientific Journal, ESJ, 2014)
This paper examines the incidence of multilingualism as a factor of language contact in the West Africa sub-region with particular reference to the interdependence between Nigeria and Benin Republic. By this symbiotic cohabitation, we hold that historically, culturally, socially and linguistically there had been an appreciable contact between the Yorubas, the Eguns of South-western Nigeria on one side and the Yorubas, the Gouns , the Fons of the Republic of Benin on the other side, before, during and after the colonial period. Bearing in mind that Nigeria was colonized by the British while Benin was colonized by the French. Thus, multilingualism as a sociolinguistics phenomenon must reflect some changes: functions, benefits and have some implications on the culture and life of the inhabitants of the region in focus. Consequently, this paper discusses the import of multilingualism across the Nigeria-Benin borders and how the socio-cultural and economic contacts had resulted in the over-all development of these communities under review.